2019
DOI: 10.1016/j.redox.2019.101220
|View full text |Cite
|
Sign up to set email alerts
|

Sodium sulfide selectively induces oxidative stress, DNA damage, and mitochondrial dysfunction and radiosensitizes glioblastoma (GBM) cells.

Abstract: Glioblastoma (GBM) has a poor prognosis despite intensive treatment with surgery and chemoradiotherapy. Previous studies using dose-escalated radiotherapy have demonstrated improved survival; however, increased rates of radionecrosis have limited its use. Development of radiosensitizers could improve patient outcome. In the present study, we report the use of sodium sulfide (Na 2 S), a hydrogen sulfide (H 2 S) donor, to selectively kill GBM cells (T98G and U87) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 73 publications
4
26
1
Order By: Relevance
“…The NaHS ability to interfere with cell cycle was already demonstrated in other cell types, such as intestinal epithelial cells [32] and in human lung fibroblasts [10]. Oxidative stress was suggested as a potential mechanism of H 2 S-induced damage; however the ROS level in NaHS-treated pVW-MSCs, investigated in the present work, demonstrated that NaHS did not induce any increase in free radicals in pVW-MSCs, differently from reports in other cell types such HT-29-CI [11]. On the other hand, we previously demonstrated that pVW-MSCs are particularly resistant to oxidative stress since lipopolysaccharide (LPS), a common ROS inducer in many cellular types, did not cause oxidative stress in pVW-MSCs [33].…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…The NaHS ability to interfere with cell cycle was already demonstrated in other cell types, such as intestinal epithelial cells [32] and in human lung fibroblasts [10]. Oxidative stress was suggested as a potential mechanism of H 2 S-induced damage; however the ROS level in NaHS-treated pVW-MSCs, investigated in the present work, demonstrated that NaHS did not induce any increase in free radicals in pVW-MSCs, differently from reports in other cell types such HT-29-CI [11]. On the other hand, we previously demonstrated that pVW-MSCs are particularly resistant to oxidative stress since lipopolysaccharide (LPS), a common ROS inducer in many cellular types, did not cause oxidative stress in pVW-MSCs [33].…”
Section: Discussioncontrasting
confidence: 68%
“…Recent interest has been addressed to the role of H 2 S in the field of mesenchymal stem cells (MSCs), so the use of H 2 S donors has been proposed to treat various pathological situations such as osteoporosis, immune disorders, inflammation and cardiovascular disease [17][18][19][20][21]. However, some H 2 S donors' adverse effects were evidenced in different cell types [10][11][12], therefore, for the safe therapeutic use of these molecules, it is necessary to consider first that very different effects could depend on the context. In the present research, we investigated the effects of a well known H 2 S donor, NaHS, on vascular stem cells isolated from the porcine thoracic aorta (pVW-MSCs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, H 2 S has also been reported to regulate cell cycle, proliferation, autophagy, apoptosis, and oxidative stress in malignant tumors (Hellmich & Szabo, ). For instance, H 2 S has been reported to selectively induce oxidative stress, DNA damage, and mitochondrial dysfunction in glioblastoma cells (Xiao et al, ). However, the function of H 2 S in carcinogenesis is controversial, as another study found that administration of H 2 S accelerated gastric cancer metastasis (Wang, Shi, et al, 2019; Wang, Tao, et al, ).…”
Section: Introductionmentioning
confidence: 99%